Discovery of High-energy and Very High Energy γ Ray Emission from the Blazar RBS 0413 - Aliu, E. (2012)
We report on the discovery of high-energy (HE; E > 0.1 GeV) and very high energy (VHE; E > 100 GeV) gamma-ray emission from the high-frequency-peaked BL Lac object RBS 0413. VERITAS, a ground-based gamma-ray observatory, detected VHE gamma rays from RBS 0413 with a statistical significance of 5.5 standard deviations and a gamma-ray flux of (1.5 ± 0.6stat ± 0.7syst) x 10^-8 photons m^-2 s^-1 (~1% of the Crab Nebula flux) above 250 GeV. The observed spectrum can be described by a power law with a photon index of 3.18 ± 0.68stat ± 0.30syst. Contemporaneous observations with the Large Area Telescope (LAT) on the Fermi Gamma-ray Space Telescope detected HE gamma rays from RBS 0413 with a statistical significance of more than 9sigmas, a power-law photon index of 1.57 ± 0.12stat +0.11 -0.12sys, and a gamma-ray flux between 300 MeV and 300 GeV of (1.64 ± 0.43stat +0.31 -0.22sys) x 10^-5 photons m^-2 s^-1. We present the results from Fermi-LAT and VERITAS, including a spectral energy distribution modeling of the gamma-ray, quasi simultaneous X-ray (Swift-XRT), ultraviolet (Swift-UVOT), and R-band optical (MDM) data. We find that, if conditions close to equipartition are required, both the combined synchrotron self-Compton/external-Compton and the lepto-hadronic models are preferred over a pure synchrotron self-Compton model.